Salvation from Below. Individuals and Grassroots Movements for Ecological Renewal - Joshtrom Isaac Kureethadam (The Francis de Sales Scientific Society (TNFS.PL), 2022)
The author argues that the lack of success in responding to the contemporary ecological crisis - the greatest of humanity's challenges today - has to do mostly with a top-down approach, as evident in international climate change negotiations. It appears that we have left the responsibility of dealing with the crisis mostly to politicians, technocrats, geo-engineers, and the lot. We have expected salvation to come from above. However, any solution to the ecological crisis will probably come from below, from committed individuals and grassroots mass movements, who can make an indispensable contribution in the restoration of our common home. The paper offers examples of some charismatic individuals and movements who have substantially contributed to addressing the challenge of the ecological crisis in our day. The article concludes with a reflection on the importance of motivating groups and individuals to care for our common home.